1997
DOI: 10.1002/(sici)1097-4547(19970915)49:6<681::aid-jnr3>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Activation of NF-?B protects hippocampal neurons against oxidative stress-induced apoptosis: Evidence for induction of manganese superoxide dismutase and suppression of peroxynitrite production and protein tyrosine nitration

Abstract: The transcription factor NF-kappaB is expressed in neurons wherein it is activated in response to a variety of stress- and injury-related stimuli including exposure to cytokines such as tumor necrosis factor-alpha (TNFalpha), and excitotoxic and oxidative insults. NF-kappaB may play a role in the anti-death actions of TNFalpha in cultured hippocampal neurons exposed to metabolic and oxidative insults. We now report that pretreatment of hippocampal cell cultures with agents that activate NF-kappaB (TNFalpha and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
301
0
2

Year Published

1998
1998
2008
2008

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 535 publications
(327 citation statements)
references
References 93 publications
24
301
0
2
Order By: Relevance
“…When pretreated with TNF, the neurons were more resistant to death when exposed to metabolic and excitotoxic insults. [57][58][59] Inhibiting NF-kB using a decoy DNA approach provided evidence that activation of NF-kB was necessary for the neuron survival-promoting action of TNF. 57 TNF pretreatment was associated with increased production of the antiapoptotic proteins Bcl-2 and Bcl-xL, and expression of a dominant negative form of IkB inhibited the ability of TNF to protect hippocampal neurons.…”
Section: Nf-jb As a Regulator Of Cell Survivalmentioning
confidence: 99%
See 2 more Smart Citations
“…When pretreated with TNF, the neurons were more resistant to death when exposed to metabolic and excitotoxic insults. [57][58][59] Inhibiting NF-kB using a decoy DNA approach provided evidence that activation of NF-kB was necessary for the neuron survival-promoting action of TNF. 57 TNF pretreatment was associated with increased production of the antiapoptotic proteins Bcl-2 and Bcl-xL, and expression of a dominant negative form of IkB inhibited the ability of TNF to protect hippocampal neurons.…”
Section: Nf-jb As a Regulator Of Cell Survivalmentioning
confidence: 99%
“…[57][58][59] Inhibiting NF-kB using a decoy DNA approach provided evidence that activation of NF-kB was necessary for the neuron survival-promoting action of TNF. 57 TNF pretreatment was associated with increased production of the antiapoptotic proteins Bcl-2 and Bcl-xL, and expression of a dominant negative form of IkB inhibited the ability of TNF to protect hippocampal neurons. 59 Stimulation of neuronal cultures through either TNFR1 or TNFR2 has been reported to lead, respectively, to either transient or lasting (4 h) activation of NF-kB.…”
Section: Nf-jb As a Regulator Of Cell Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, NF-κB is an inducible transcription factor that initiates the subsequent expression of several inflammatory molecules [12,13]. Several studies now indicate that neuronal expression of NF-κB is induced by a variety of insults, including TNF and mechanical injury and that this neuronal induction is associated with subsequent neuronal expression of inducible nitric oxide synthase (INOS) and superoxide dismutase (SOD) [14][15][16][17].…”
Section: Neurons As Inflammatory Response Cells?mentioning
confidence: 99%
“…Activation of ERK1/2, CREB, and NF-κB can enhance anti-apoptic actions by inducing expression of anti-apoptotic Bcl-2 proteins and antioxidant enzymes such as manganese superoxide dismutase (SOD2) that protect against superoxide radicals (Hetman and Gozdz, 2004;Hinerfeld et al, 2004;Martinou et al, 1994;Mattson et al, 1997;Mattson and Meffert, 2006). The increased levels of ERK1/2, CREB, and NF-κB coupled with the increased levels of the neuronal protein enolase and glial protein GFAP suggested that these downstream neuroprotective proteins could also be altered by chronic CXCL10.…”
Section: Chronic Cxcl10 Increases Expression Of Anti-apoptotic Proteimentioning
confidence: 99%